Understanding patients’ lived experiences: the interrelationship of rhetoric and hermeneutics - Finch, Linda P. (Nursing philosophy, 2004)
Understanding each patient's situation or lived experience evolves from a nurse's sincere communication with the patient. Through rhetoric, the nurse's use of competent language and expressions is more likely to engage the patient in a dialogical discussion that brings forth an open, honest display of feelings and emotions. Through hermeneutics, the nurse gains an accurate understanding and interpretation of a patient's beliefs, values, and situations that supports explanations of meaning. Thus, with rhetoric being the words or expressions that give rise to hermeneutics or the interpretation, the blending of the two creates a rhetorical-hermeneutical relationship that provides accurate understanding of a patient's true lived experience. Consequently, knowing the patient depends upon the nurse's rhetorical competence and accurate assessment of each patient's authentic self. Nurses should seek to interpret and understand the lived experiences of patients in order to limit or prevent misunderstandings and inaccuracies in communication. The truth that emerges from the expressed rhetorical-hermeneutical interrelationship will enhance nurses’ sensitivity to patient matters, produce relationship outcomes that emerge from a consistent and effectively applied set of interpersonal principles, and more importantly, successfully influence nurses’ lives and those of their patients with meaning that ultimately improves the human condition. Thus, nurses’ communication and perceptive understanding of each patient's world or lived experience becomes an integral and necessary component to effectively carrying out the practice role of caregiving.